Corporate Social Responsibility and Consumer Emotional Marketing in Big Data Era: A Mini Literature Review - Shao, Jing; Zhang, Tianzi; Wang, Haohui; Tian, Yuanhao (Frontiers in Psychology, 2022)
In the digital era, big data can strengthen the awareness of corporate social responsibility (CSR) and make CSR more transparent to consumers. While big data continues to deepen the business transformation of enterprises, it is also a process of constantly understanding consumption and public expectations. In this process, the cognitive structure of enterprises is constantly adjusted, no longer simply pursuing performance but constantly realizing the expectations of users and society in order to maintain performance. Through mass media, corporate media, and other platforms, CSR is easier to affect consumers’ emotions. By reviewing the theory of emotional marketing and related research, this paper focuses on the different emotional ties between CSR and consumers and their different effects on consumers. This paper further emphasizes the profound significance of emotional marketing theory for understanding CSR in the era of big data. In addition, this paper also calls for more research based on big data technology, broken down by consumer needs - more specific attention to the different impacts of CSR on different consumers.